Gonadal hormones affect alcohol drinking, but not cue+yohimbine- induced alcohol seeking, in male and female rats - Bertholomey, Megan L. (Physiol Behav, 2017)
Alcohol use disorder (AUD) is a chronic, relapsing disease characterized by maladaptive patterns of alcohol drinking and seeking. Though sex differences exist in the etiology of AUD, much remains to be elucidated concerning the mechanisms underlying sex-related vulnerability to developing excessive alcohol-motivated behavior. While a large body of evidence points to an important role of circulating gonadal hormones in mediating cocaine reinforcement, findings are less consistent with respect to ethanol. Critically, the effects of gonadal hormones on the reinstatement of ethanol seeking, a model of “craving”-like behavior that reveals pronounced sex differences, has not yet been examined. Thus, the goal of the present experiment was to directly compare manipulations of gonadal hormones in male and female rats on ethanol-motivated behavior. Rats received sham or gonadectomy surgery with or without hormone replacement prior to and throughout three weeks of operant ethanol self-administration to determine the effects of chronically high or low gonadal hormone levels on ethanol drinking. Hormone treatment ceased during extinction training, and the effects of an acute injection of either testosterone (in males) or estradiol (in females) on cue+yohimbine-induced reinstatement of ethanol seeking was determined. Separate groups of gonadally- intact female rats went through similar training, but the effects of either the antiestrogen, fulvestrant, the selective estrogen receptor modulator, clomiphene, or the estrogen receptor β antagonist, PHTPP, on the reinstatement of ethanol seeking were determined. Chronic estradiol replacement produced significant increases in ethanol drinking in female rats, while chronic testosterone significantly decreased ethanol drinking in male rats. Gonadectomy alone only produced modest shifts in drinking towards the opposite-sex pattern, and did not eliminate the robust sex differences that persisted regardless of hormone manipulations. Neither prior chronic nor acute hormone manipulations altered cue+yohimbine-induced reinstatement of ethanol seeking, though blockade of estrogen receptors tended to reduce reinstatement in gonadally- intact females. Overall, our findings indicate that gonadal hormones at least partially mediate, but do not totally account for the sex differences evident in ethanol self-administration, and circulating gonadal hormones have little effect on the reinstatement of ethanol seeking. These results provide a foundation for future studies examining the neuronal mechanisms underlying sex differences in ethanol drinking and seeking.